The cartoons that shook the world - Klausen, Jytte (Yale University Press, 2009)
"On September 30, 2005, the Danish newspaper Jyllands-Posten published twelve cartoons of the Prophet Muhammad. Five months later, thousands of Muslims inundated the newspaper with outpourings of anger and grief by phone, email, and fax; from Asia to Europe Muslims took to the streets in protest. This book is the first comprehensive investigation of the conflict that aroused impassioned debates around the world on freedom of expression, blasphemy, and the nature of modern Islam"--Publisher.